The effect of confounding variables on the relationship between anthropometric and physiological features in 2000-m rowing ergometer performance - Podstawski, Robert; Borysławski, Krzysztof; Alföldi, Zoltán; Ferenc, Ihász; Wąsik, Jacek (Frontiers in Physiology, 2023)
Background: Anthropometric and physiological characteristics are often considered as potential variables that are significantly related with motor performance. Aim. The aim of this study was to apply a different and rarely used methodological approach to evaluate the relationships between anthropometric and physiological characteristics vs. 2000-m rowing ergometer performance. Methods: The study involved 70 best female and 130 best male rowers from the seven largest Hungarian rowing clubs, classified into one of the following age categories: juniors (36 women and 55 men, age range: 15-16 years), older juniors (26 women and 52 men, age range: 17-18 years), and seniors (8 women and 23 men, age range: over 18 years). A statistical analysis was carried out based on the partial correlations between a pair of variables that accounted for the relationships with another (third) variable (first-order partial correlation) or several (n) other variables (n-order partial correlation). Results: An increase in skeletal muscle mass was associated (r = -.39, p<.001) with a significant decrease in rowing time over a distance of 2000 m, whereas a significant increase in rowing time was noted with an increase in sitting height (only in men, r = .33, p<.001), body mass (in women and men: r = .24, p = .013 and r = .31, p = .009), and body fat percentage (r = .26, p < .030). Rowing time was also bound by a significant correlation with maximal force (r = -.79 and -.90, p<.001) and relative maximal power (r = -.54 and -.78, p<.001) in both sexes, with relative peak power in males (r = -.51, p < .001), and with estimated relative maximal aerobic capacity in females (r = -.43, p <.001). Conclusions. Rowing performance over a distance of 2000 m is significantly influenced by the increased values of skeletal muscle mass, maximal force, relative maximal power, relative peak power, and estimated relative maximal aerobic capacity.